2008
DOI: 10.5424/sjar/200806s1-391
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic control of flowering time: a review

Abstract: The rotation of the earth results in periodic changes in environmental factors such as daylength and temperature; the circadian clock is the endogenous mechanism responsible for day-length measurement, and allows plants to anticipate these fluctuations and modulate their developmental programs to maximize adaptation to those environmental cues. Flowering represents the transition from a vegetative to reproductive phase and is controlled by complex and highly regulated genetic pathways. In many plants, the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 211 publications
(252 reference statements)
0
13
0
2
Order By: Relevance
“…GI, which promotes CO, also promotes LATE ELONGATED HYPOCOTYL (LHY) upregulation of TOC1 in a ''three-loop model of the circadian clock'' in A. thaliana (Lagercrantz 2009), where LHY in turn suppresses GI and promotes PRR7 and PRR9. PRR7 and PRR9 have been shown to suppress LHY (Lagercrantz 2009) and have been reported to upregulate CO through suppression of CDF1, a repressor of CO (Jarillo et al 2008). COL-2 could also be upregulated in a similar fashion (Fig.…”
Section: Model Integrating Floral and Dormancy Developmentmentioning
confidence: 87%
“…GI, which promotes CO, also promotes LATE ELONGATED HYPOCOTYL (LHY) upregulation of TOC1 in a ''three-loop model of the circadian clock'' in A. thaliana (Lagercrantz 2009), where LHY in turn suppresses GI and promotes PRR7 and PRR9. PRR7 and PRR9 have been shown to suppress LHY (Lagercrantz 2009) and have been reported to upregulate CO through suppression of CDF1, a repressor of CO (Jarillo et al 2008). COL-2 could also be upregulated in a similar fashion (Fig.…”
Section: Model Integrating Floral and Dormancy Developmentmentioning
confidence: 87%
“…Photoperiod controls not only flowering [17] but also seed germination, stem and leaf growth, assimilate portioning and secondary metabolism [3]. And in this study photoperiod influenced height plant, diameter of stem, number and color of roselle leaves.…”
Section: Resultsmentioning
confidence: 97%
“…This is despite the high similarity between the PHYA locus in Arabidopsis rice, sorghum and maize [62] suggesting that a similar response would be expected. However, PHYA mutations in combination with PHYB or PHYC cause early flowering in rice [61]. In addition, studies have shown that PHYC plays an essential role in the acceleration of wheat flowering under LD photoperiods.…”
Section: Photoreceptors Involved In Flowering Timementioning
confidence: 99%
“…Plants use many photoreceptors to detect the intensity and quality of light, including PHYTOCHROMES (PHY), which absorb the red and far-red region of the visible spectrum, and the CRYPTOCHROMES (CRY) [63]. Arabidopsis contains five PHYs (A-E), where accumulation of CO in LD is due to stabilization mediated by phytochrome A (PHYA), cryptochromes (CRY1/2) and SUPPRESSOR OF PHYA-105 (SPA1) [61]. However, it has been shown that PHYB signals delay flowering by destabilizing CO protein during the morning and have an inhibitory effect on FT expression [60].…”
Section: Photoreceptors Involved In Flowering Timementioning
confidence: 99%
See 1 more Smart Citation